Mechanical soy bean washing improves the performance of tempe crafters - Anizar, Anizar; Torong, Zainul Bahri (Talenta Publisher, 2020)
The business of making tempe every day processes 50 kg of soybeans into tempeh done manually with 4 craftsmen. But the washing of soybeans is one of the most tiring activities because the crafters have to lift buckets filled with soybeans and water so that the weight of the bucket is quite heavy. The process of washing soybeans starts from the step of pouring 10 kg of soybeans into a bucket, giving water, stirring, lifting the bucket to pouring the water in the bucket. Washing the soybeans until clean is done by the craftsman continuously up to 5 times. Processing 50 kg of soybeans causes the craftsman to carry out the process of washing soybeans 25 times each day. The craftsman complains of back pain and both arms and sometimes the craftsman does not come to work if the pain is unbearable. Utilization of soybean washing tools can reduce the washing time so that the process can be completed more quickly and the crafters do not experience pain complaints. Mechanical soybean washing causes shorter washing time for soybeans, faster work, cleaner soybeans and crafters free from complaints of back pain.